2014
DOI: 10.1002/app.41787
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical properties and thermal stability of recycled cellulose reinforced starch–gelatin polymer composite

Abstract: Samples of starch−gelatin polymer reinforced with 5% of recycled cellulose were prepared using an extrusion‐compression molding process. Nanoindentation and atomic force acoustic microscopy (AFAM) techniques were used to study the effect of reinforcement at nanoscale level. Nanoindentation tests show a 163% increase in hardness and 123% of elastic modulus enhancement after recycled cellulose inclusion. AFAM shows that distribution of recycled cellulose into the polymer matrix is rather homogeneous at nanoscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 65 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Finally, starch/cellulose blends can be cross-linked by REx, which allows obtaining innovative materials with improved properties and one hundred percent biodegradable from natural resources. In this context, recently Rodríguez-Castellanos et al [155] reported this behavior for different cellulose-reinforced starchgelatin polymer composites. Tests showed an increase of 163 % in hardness and 123 % of elastic modulus enhancement after recycled cellulose inclusion.…”
Section: Reactive Extrusion Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Finally, starch/cellulose blends can be cross-linked by REx, which allows obtaining innovative materials with improved properties and one hundred percent biodegradable from natural resources. In this context, recently Rodríguez-Castellanos et al [155] reported this behavior for different cellulose-reinforced starchgelatin polymer composites. Tests showed an increase of 163 % in hardness and 123 % of elastic modulus enhancement after recycled cellulose inclusion.…”
Section: Reactive Extrusion Methodsmentioning
confidence: 74%
“…Atomic force acoustic microscopy showed that distribution of recycled cellulose in the polymer matrix is rather homogeneous at nanoscale, which improved load transfer. According to the authors [155], thermogravimetric analysis indicated an increase in thermal stability of the cellulose-reinforced polymer matrix samples.…”
Section: Reactive Extrusion Methodsmentioning
confidence: 99%
“…The analysis of the resonance frequencies of the system allow one to evaluate the indentation modulus of an elastic sample (Passeri et al, 2007), while the simultaneous acquisition of the resonance frequencies and the corresponding quality factors enable the evaluation of the complex elastic modulus, i.e., storage and loss moduli and the loss tangent, of viscoelastic materials (Yuya, Hurley, & Turner, 2011). CR-AFM was used to study the effect of reinforcement of starch-gelatin polymers through recycled cellulose at nanoscale level, evaluating the elastic modulus of the reinforced material and studying the homogeneity of the distribution of the cellulose into the polymer matrix (Rodríguez-Castellanos, Flores-Ruiz, Martínez-Bustos, Chiñas-Castillo, & Espinoza-Beltrán, 2015).…”
Section: Nanomechanical Characterization Of Food Packaging Surfacesmentioning
confidence: 99%
“…Müller et al reported that adding cellulose fibers in starch-based films decreased its susceptibility to ambient humidity, and at the same time improved the mechanical properties of the films [41]. Previous studies had showed that cellulose can improve the mechanical properties of gelatin-starch matrix due to chemical compatibility [46] reducing the aging effect of retrogradation. The micrographs presented in Figure 4 show the formation a polymer matrix containing starch, gelatin and glycerol as plasticizer with cellulose.…”
Section: Cellulose Additionmentioning
confidence: 99%